1915 Wyo. Sess. Laws 91, ch. 91, § 13 - (:unkn) unknown (General Publisher, 1915)
Required noncitizens to purchase a specified license before owning or possessing any firearm or fishing tackle.
--
Keywords: REGISTRATION